Cutting tool

CN123036398APending Publication Date: 2026-11-03MITSUBISHI MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580024370.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-26
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Ceramic cutting tools have insufficient wear resistance and chip resistance during high-speed cutting, especially when the tool tip generates a lot of heat, they are prone to abnormal damage such as thermal wear, oxidative wear, abrasive wear and boundary damage.

Method used

A first hard phase with low oxidation resistance and a second hard phase with high oxidation resistance are dispersed in a cermet cutting tool matrix. The hardness distribution is adjusted on and around the surface. The Vickers hardness reaches 1700-2100 Hv in the region from the surface to a depth of 40 μm and 1600-1780 Hv in the interior to a depth of 600 μm. The Cr content in the bonding phase is controlled to improve oxidation resistance.

Benefits of technology

Under high-speed cutting conditions, it significantly improves the wear resistance and chip resistance of cutting tools, effectively suppresses abnormal damage, and extends the service life of tools.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123036398A_ABST
    Figure CN123036398A_ABST
Patent Text Reader

Abstract

A cutting tool having a substrate whose first hard phase is a complex carbonitride containing 3.0 mass% or less of one or more selected from Zr, V, Nb, Ta, Mo and W, less than 0.2 mass% of Cr, 18.0 to 22.0 mass% in total of C and N, and the balance of Ti and inevitable impurities, whose second hard phase is a complex carbonitride containing 10.0 to 25.0 mass% of one or more selected from Zr, V, Nb, Ta, Mo and W, more than 0.0 mass% and less than 1.0 mass% (more than the content of the first hard phase) of Cr, 15.0 to 20.0 mass% in total of C and N, and the balance of Ti and inevitable impurities, whose binder phase contains less than 5.0 mass% in total of Ni and Fe, 1.0 to 8.0% of Cr in terms of mass ratio relative to the Co content, and the balance of Co and inevitable impurities, the Vickers hardness monotonously decreasing from the relief to the inside to 100 μm, being 1700 to 2100 Hv to the inside to 40 μm from the relief, and being 1600 to 1780 Hv at a position 600 μm inside from the relief.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to cutting tools made of cermet-based materials. This application claims priority to Japanese Patent Application No. 2024-54388, filed March 28, 2024. All matters described in that application are incorporated herein by reference. Background Technology

[0002] In addition to WC-based cemented carbide, cermets based on Ti carbides, carbonitrides, and carbonitrides are also used as the base material for cutting tools.

[0003] For example, there exists a TiCN-based cermet, in which iron group elements are the main components of the bonding phase, TiCN is the main component of the hard phase, and further contains carbides, nitrides, and carbonitrides of metals from groups 4, 5, and 6 of the periodic table.

[0004] Compared with WC-based cemented carbide substrates, the matrix of cermet cutting tools has poorer strength and toughness. Therefore, a solution has been proposed to improve wear resistance and chipping resistance by adjusting the hardness of the surface layer of the substrate.

[0005] For example, Patent Document 1 describes a substrate for a cermet cutting tool, which has a region with a Vickers hardness of 2000 or higher extending from the surface to an interior of 50 μm. This substrate has excellent wear resistance, especially when used for cutting cast iron.

[0006] Additionally, for example, Patent Document 2 describes a substrate for a cermet cutting tool, which has a region of reduced bonding phase extending from the surface of the sintered body to an interior of 30 to 200 μm, and a region with a Vickers hardness of 1800 or higher extending from the surface of the sintered body to an interior of 30 μm. This substrate has excellent wear resistance and chip resistance, and the surface roughness of the finished workpiece is small.

[0007] Patent Document 1: Japanese Patent No. 2628200

[0008] Patent Document 2: Japanese Patent No. 5644388 Summary of the Invention

[0009] The present invention was made in view of the above circumstances and the above solution, and its object is to provide a cutting tool with a cermet matrix that has excellent wear resistance and chip resistance even in high-speed cutting, such as cutting speeds of 200 m / min or higher, where the tip heat generation is high.

[0010] The cutting tools based on the substrate involved in the embodiments of the present invention are made of cermet.

[0011] The matrix comprises a first hard phase, a second hard phase, and a bonding phase.

[0012] The first hard phase is a composite carbonitride comprising 0.0–3.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, 0.0% by mass and less than 0.2% by mass of Cr, 18.0–22.0% by mass of C and N, with the remainder being Ti and unavoidable impurities.

[0013] The second hard phase is a composite carbonitride comprising a total of 10.0–25.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, greater than 0.0% by mass and less than 1.0% by mass of Cr (wherein the Cr content of the second phase is greater than that of the first hard phase), a total of 15.0–20.0% by mass of C and N, with the remainder being Ti and unavoidable impurities.

[0014] The bonding phase comprises a total of 0.0% by mass and less than 5.0% by mass of Ni and Fe, 1.0% to 8.0% by mass relative to the Co content, and the remainder is Co and unavoidable impurities.

[0015] In a first region extending 100 μm into the interior of the substrate from the flank face, the Vickers hardness decreases monotonically. In a second region extending 40 μm into the substrate from the flank face, the Vickers hardness is 1700–2100 Hv. At a location extending 600 μm into the interior of the substrate from the flank face, the Vickers hardness is 1600–1780 Hv.

[0016] The cutting tool can satisfy any one or more of the following (1) to (3).

[0017] (1) The second hard phase further comprises: Ta and / or Nb; and W.

[0018] (2) Further having a third hard phase, the third hard phase being a composite carbonitride comprising a total of 25.0 to 45.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo and W, 0.0% by mass and less than 1.0% by mass of Cr (wherein less than the Cr content of the second hard phase), a total of 10.0 to 17.0% by mass of C and N, the remainder being Ti (wherein less than the Ti content of the first hard phase) and unavoidable impurities.

[0019] (3) The area ratio of the first hard phase is 10.0 to 30.0%, the area ratio of the second hard phase is 50.0 to 80.0%, and the area ratio of the third hard phase is 0.0 to 5.0%.

[0020] The cutting tools with a cermet substrate involved in the aforementioned embodiments exhibit excellent wear resistance and chip resistance, even under cutting conditions where the cutting tip generates high heat during high-speed cutting. Attached Figure Description

[0021] Figure 1 This is a schematic diagram illustrating an example of the microstructure of a cutting tool with a cermet substrate, as described in an embodiment of the present invention.

[0022] Figure 2 This is a schematic diagram of another example of the microstructure of a cutting tool with a cermet matrix, which is involved in other embodiments of the present invention.

[0023] Figure 3 This is a schematic diagram showing an example of the measuring surface when measuring Vickers hardness.

[0024] Figure 4 yes Figure 3 Top view.

[0025] Figure 5 This is an example of a graph (schematic diagram) showing the frequency and cumulative relative frequency distribution of the brightness of each pixel at 256 gray levels obtained by observing the microstructure of a cutting tool with a cermet substrate according to an embodiment of the present invention through SEM. Detailed Implementation

[0026] In high-speed cutting processes where the cutting tip generates a lot of heat, cutting tools with a cermet matrix need to suppress abnormal damage such as thermal wear, oxidative wear, abrasive wear, and boundary damage.

[0027] The inventors have discovered that if only a surface hardening layer caused by a reduction in the Co content of the bonding phase exists on and near the surface of a cermet cutting tool substrate (hereinafter sometimes referred to as the substrate), the anti-oxidative wear during cutting is insufficient and cannot adequately suppress the aforementioned abnormal damage.

[0028] Therefore, the inventors conducted further research, and as a result, they obtained the following insights (1) to (4) as a strategy for improving the durability of cermet-based matrices during machining.

[0029] 1) In order to prevent the aforementioned abnormal damage, it is preferable to disperse a first hard phase with low oxidation resistance and a second hard phase with high oxidation resistance as a hard phase in the matrix.

[0030] Here, the first hard phase is a composite carbonitride containing Ti but not Cr, and the second hard phase is a composite carbonitride containing both Ti and Cr. Furthermore, the composition of these composite carbonitrides is not limited to stoichiometric compositions.

[0031] 2) If a highly antioxidant bound phase is further dispersed in the matrix, oxidative wear is further suppressed. To obtain this highly antioxidant bound phase, it is preferable to contain Cr.

[0032] 3) In order to suppress abrasive wear, it is preferable that the surface and the vicinity of the substrate have high hardness. For this purpose, it is preferable to add the aforementioned first hard phase to the surface and the vicinity of the substrate so that the Vickers hardness reaches 1700Hv or more in a region from the surface to the interior of 40μm.

[0033] 4) To suppress abnormal damage such as boundary damage, it is necessary to set specific hardness for the surface and surrounding areas of the matrix and for the internal hardness of the matrix, and also to ensure that the composition of the bonding phase is one that improves toughness. The former is achieved by monotonically decreasing the Vickers hardness from the surface to 100 μm and setting the Vickers hardness of the matrix to a specified hardness. The latter is achieved by ensuring that the bonding phase is free of Ni and Fe (the total content of Ni and Fe in the bonding phase should be less than 5.0% by mass).

[0034] This invention is derived based on these insights.

[0035] The following is a detailed description of the metal-ceramic cutting tool according to embodiments of the present invention.

[0036] It should be noted that in this specification and claims, when "L~M" (where L and M are both numerical values) is used to represent a numerical range, its meaning is the same as "above L and below M," and the range includes the upper limit (M) and the lower limit (L). When only the unit of the upper limit (M) is specified, the unit of the upper limit (M) is the same as the unit of the lower limit (L). The average value is the arithmetic mean.

[0037] The cermet cutting tools described in the claims and this specification may or may not have a known coating on the substrate.

[0038] 1. The structure and composition of the matrix

[0039] The cross-sectional microstructure of the matrix of the metal-ceramic cutting tool according to the embodiments of the present invention will be described. Figure 1 This is an example schematically illustrating the cross-sectional structure of a matrix according to an embodiment of the present invention. According to Figure 1The matrix of a cermet cutting tool must contain a first hard phase 1, a second hard phase 2, and a bonding phase 3. The first hard phase 1 can be located inside the second hard phase 2. Furthermore, Figure 2 This is an example, schematically illustrating the cross-sectional microstructure of the substrate of a cermet cutting tool according to other embodiments of the present invention. According to Figure 2 In addition to the second hard phase 2, the first hard phase 1 also has a third hard phase 4.

[0040] Although the matrix of the cermet cutting tool of the present invention is manufactured such that no other phases exist besides the hard phase (first hard phase, second hard phase, third hard phase) and the bonding phase, these other phases (e.g., carbide phase, nitride phase) may be unintentionally generated in part during the manufacturing process.

[0041] (1) Hard phase

[0042] In a hard phase, a first hard phase and a second hard phase must exist, while a third hard phase may or may not exist.

[0043] The first hard phase is a complex carbonitride comprising 0.0 to 3.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, 0.0% by mass and less than 0.2% by mass of Cr, 18.0 to 22.0% by mass of C and N, with the remainder being Ti and unavoidable impurities. The Ti content of the first hard phase is more preferably 78.0 to 80.0% by mass. Here, 0.0 to 3.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W means that it may or may not contain one or more of Zr, V, Nb, Ta, Mo, and W; when contained, the maximum total content of at least one selected from Zr, V, Nb, Ta, Mo, and W is 3.0% by mass. The definition of the total content when at least one selected from Zr, V, Nb, Ta, Mo, and W is included in the second and third hard phases is the same.

[0044] The first hard phase is a phase with excellent wear resistance.

[0045] The second hard phase is a complex carbonitride comprising a total of 10.0 to 25.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, less than 1.0% by mass of Cr (which is more than the Cr content of the first hard phase), a total of 15.0 to 20.0% by mass of C and N, with the remainder being Ti and unavoidable impurities. The Ti content of the second hard phase is more preferably 60.0% by mass or more and less than 68.0% by mass.

[0046] The second hard phase is a phase with excellent antioxidant properties.

[0047] The third hard phase is a complex carbonitride comprising a total of 25.0–45.0% by mass of Zr, V, Nb, Ta, Mo, and W, 0.0% by mass and less than 1.0% by mass of Cr (which is less than the Cr content of the second hard phase), a total of 10.0–17.0% by mass of C and N, with the remainder being Ti (which is less than the Ti content of the first hard phase) and unavoidable impurities. The Ti content of the third hard phase is more preferably 40.0–60.0% by mass.

[0048] The third hard phase is a phase with excellent fracture toughness, which improves the tool's resistance to chipping.

[0049] The Zr, V, Nb, Ta, Mo and W contribute equally to the improvement of hardness and the improvement of damage resistance (toughness), with Ta and / or Nb and W being particularly preferred.

[0050] The composition of the first hard phase, the second hard phase, and the third hard phase is such that the sum of the elements constituting the composite carbonitrides of each hard phase is set to 100 by mass.

[0051] The area fraction of the first hard phase in any cross section or surface of the matrix is ​​more preferably 10.0% to 30.0%, and even more preferably 15.0% to 25.0%. The area fraction of the second hard phase is more preferably 50.0% to 80.0%, and even more preferably 60.0% to 75.0%. The area fraction of the third hard phase is more preferably 0.0% to 5.0%, and even more preferably 0.0% to 3.0%. The identification method for each hard phase will be described later.

[0052] (2) Combining phase

[0053] The composition of the bound phase is composed of Ni and Fe totaling more than 0.0% by mass and less than 5.0% by mass, Cr in a mass ratio of 1.0% to 8.0% relative to Co content, and the remainder being Co and unavoidable impurities.

[0054] The oxidation resistance of the matrix is ​​improved by including Cr in the bonding phase. If the Cr content in the bonding phase is 1.0 to 8.0% by mass ratio to the Co content in the bonding phase, the oxidation resistance of the matrix of cermet cutting tools is reliably improved.

[0055] Examples of unavoidable impurities sometimes include components contained in the first to third hard phases in the combined phase.

[0056] The area fraction of the bound phase in the cross section or surface of the matrix (excluding the area near the surface for measurement because the area fraction of the bound phase is low near the surface) is more preferably 6.0 to 13.0%, and even more preferably 8.0 to 12.0%.

[0057] (3) Composition

[0058] The composition of the matrix as a whole can be illustrated by the following examples.

[0059] 1) Co: 10.0-15.0% by mass, Cr: 0.5-1.5% by mass, and the total of at least one of Zr, V, Nb, Ta, Mo and W: 15.0-40.0% by mass, C: 5.0-10.0% by mass, N: 6.0-12.0% by mass, with the remainder being Ti and unavoidable impurities.

[0060] 2) In the above 1), it further contains 7.0 to 25.0% by mass of W and 0.5 to 1.0% by mass of Cr.

[0061] 2. Vickers hardness

[0062] To prevent abrasive wear and boundary damage, the flank face of the cermet substrate preferably has a specified Vickers hardness.

[0063] The Vickers hardness referred to in the claims and this specification refers to the value measured according to JIS Z 2244:2009 with a test weight of 4.9 N (500 gf).

[0064] In the first region extending 100 μm into the matrix from the flank face, the Vickers hardness decreases monotonically. In the second region extending 40 μm into the matrix from the flank face, the Vickers hardness is 1700–2100 Hv. In the third region extending 600 μm into the matrix from the flank face, the Vickers hardness is 1600–1780 Hv.

[0065] The reasons for favoring this Vickers hardness are as follows. If the Vickers hardness does not decrease monotonically in the first region extending 100 μm into the matrix from the flank face, the flank wear of the cutting tool increases. If the Vickers hardness in the second region extending 40 μm into the matrix from the flank face is less than 1700 Hv, the flank wear of the cutting tool increases; if the Vickers hardness is 2100 Hv or higher, the frequency of boundary damage increases. Furthermore, if the Vickers hardness from the flank face to a depth of 600 μm is less than 1600, the flank wear of the cutting tool increases; if it exceeds 1780 Hv, the cutting tool is prone to chipping during high-speed cutting.

[0066] In the claims and in this specification:

[0067] In the first region extending 100 μm into the matrix from the flank face, the Vickers hardness monotonically decreases, meaning that at depths of 10 μm, 40 μm, and 100 μm into the matrix from the flank face, the Vickers hardness (Hv) monotonically decreases. That is, there is one or more locations where the Vickers hardness (Hv) decreases in the direction of deepening, and even at locations where the Vickers hardness does not decrease, the Vickers hardness does not increase.

[0068] In the second region extending 40 μm into the matrix from the flank face, a Vickers hardness of 1700–2100 Hv means that the Vickers hardness (Hv) at depths of 10 μm and 40 μm from the flank face is 1700–2100 Hv.

[0069] 4. Method for determining Vickers hardness

[0070] Reference Figure 3 and Figure 4 The method for determining Vickers hardness is explained.

[0071] 1) Select the flank face of the cutting tool used to determine the hardness.

[0072] 2) such as Figure 3 As shown, a grinding portion 12 is provided on a part of the surface 10 at an angle φ (an angle 11 that is easy to measure hardness, which is more than 5 degrees and less than 20 degrees). The surface 10 on which the grinding portion 12 is provided has an un-grinded portion 13.

[0073] 3) Select a magnification of about 5 times and set an observation field of view of, for example, 0.9 mm (vertical) × (0.9~1.2) mm (horizontal) that can visually identify multiple hard phases. The observation field of view includes the polished part 12 and the unpolished part 13.

[0074] 4) such as Figure 3 As shown, in this field of view, observe the tiny bumps and depressions at the boundary between the polished part 12 and the unpolished part 13, and draw the line segment X connecting the two ends of the tiny bumps and depressions in this field of view.

[0075] 5) Draw the surface line S of the deepest part, which is parallel to the line segment X and tangent to the innermost point (deepest part) of the grinding part among the micro-bumps. This line segment S is regarded as the reference position of the flank face surface (hereafter, the reference position of the surface line segment and the flank face surface will not be distinguished). The surface line segment S does not intersect the aforementioned micro-bumps outside the deepest part.

[0076] 6) Draw a line segment A on the grinding section 12, starting from the outermost surface line segment S and moving away from it by 10 / sinφμm. The center of each indentation is located on line segment A. Set seven measurement points a at 150μm intervals (in... Figure 4Only five points are explicitly shown in the text. Vickers hardness is measured at these points (the measurement location corresponds to a depth of (10 / sinφ)×sinφ=10μm inside the base of the cutting tool, at a distance from the outermost surface segment B). The average value 'a' is calculated from the values ​​of the five points after removing the maximum and minimum values. Furthermore, in... Figure 4 The image shows the locations where the Vickers hardness was measured at these five points.

[0077] Using the same method, line segment B is drawn on the grinding section 12 at a position 40 / sinφμm away from the outermost surface line segment S, and line segment C is drawn at a position 100 / sinφμm away. The center of each indentation is located on line segments B and C. Seven measurement points b and c are set at 150μm intervals. Figure 4 Only five points are explicitly shown in the figure. Vickers hardness is measured at these measurement points (the measurement locations of these hardness measurements are equivalent to the depths of the cutting tool's matrix at distances of 40 μm and 100 μm from the outermost surface line segment B, respectively). The average values ​​b and c of the five points after removing the maximum and minimum values ​​are calculated.

[0078] 8) The area on the grinding part 12 extending 600 / sinφμm or more from the outermost surface line segment S is defined as the internal region, and the average Vickers hardness of this region is taken as the representative value of the hardness of the internal region. The hardness of the internal region is obtained as follows: A line segment D parallel to the outermost surface line segment S is drawn on the grinding part 12 at a position 600 / sinφμm or more away from the outermost surface line segment S. The center of each indentation is located on line segment D, and seven measurement points d are set at 150μm intervals. Figure 4 Only five points are explicitly shown in the text. Vickers hardness is measured at these points, and the average value d is calculated from the values ​​of the five points after removing the maximum and minimum values. Furthermore, in... Figure 4 The image shows the locations where the Vickers hardness was measured at these five points.

[0079] 4. Methods for confirming composition

[0080] The analytical method for non-metallic components in the matrix is ​​as follows. First, the matrix is ​​pulverized into powder. Then, carbon is quantitatively analyzed by non-dispersive infrared analysis, nitrogen is quantitatively analyzed by thermal conductivity, and oxygen (oxygen as an unavoidable impurity) contained in the raw material powder or introduced by the oxidation of the raw material powder is quantitatively analyzed by infrared absorption analysis to determine the mass contained in the matrix.

[0081] Next, regarding the metallic composition of the matrix, the matrix was cut to obtain any cross-section that could ensure a 5mm × 5mm observation surface. After grinding 1mm in depth and further mirror polishing, the cross-section was analyzed using X-ray fluorescence (XRF). The mass percentage of each metallic element was multiplied by the mass percentage of the total content of carbon, nitrogen, and oxygen (subtracted from 100%), and this value was taken as the mass percentage of each metallic element in the matrix.

[0082] The calculation would be illustrated as follows:

[0083] When the combined mass percentage of carbon, nitrogen, and oxygen is 20% by mass, and the Ti content obtained by XRF analysis is 80% by mass,

[0084] The Ti content in the matrix of the cutting tool is 80 × (100 - 20) = 64 (mass%).

[0085] 5. Identification of each phase and area ratio

[0086] The identification of each phase was performed using a scanning electron microscope (SEM) and an electron probe microanalyzer (EPMA).

[0087] First, the matrix is ​​mirror-polished in any field of view (preferably 18μm (vertical) × 24μm (horizontal) or larger, with each phase containing at least 15 phases) so as not to interfere with SEM observation and EPMA composition analysis.

[0088] Next, the cross-section after mirror polishing was observed using SEM to obtain a reflected electron image composed of pixels with a brightness of 256 gray levels (0 for black and 255 for white). A histogram was plotted with brightness on the horizontal axis and the number of pixels with that brightness on the vertical axis. Figure 5 The solid line represents the pixel occurrence frequency (number of occurrences), and the dashed line represents the cumulative relative frequency (cumulative relative number of occurrences). Using this graph, thresholds are set as follows to distinguish phases. Here, the interval between pixels can be exemplified as 20nm in both the horizontal and vertical directions.

[0089] Identification and area ratio of phases considered as the first hard phase

[0090] Below, refer to Figure 5 Please provide an explanation.

[0091] Pixels from luminance A (closest to black, greater than 0) to the intermediate luminance D (called the left threshold D) between luminance B (corresponding to 5.0% cumulative relative frequency) and luminance C (corresponding to the maximum frequency) are considered to belong to the first hard phase. The area fraction of the first hard phase is calculated by dividing these pixels by the total number of pixels in the entire field of view.

[0092] To be on the safe side, EPMA analysis was performed at the locations of these pixels to confirm that the composition of the first hard phase described above was met.

[0093] Identification and area ratio of phases considered as the second hard phase

[0094] The pixels within the range between the luminance immediately to the right of the left threshold D and the intermediate luminance value F (called the right threshold F) corresponding to the luminance E at 97.0% cumulative relative frequency are considered to belong to the second hard phase. The area fraction of the second hard phase is calculated by dividing these pixels by the total number of pixels.

[0095] To be on the safe side, EPMA analysis was performed at the locations of these pixels to confirm that the composition of the aforementioned second hard phase is satisfied.

[0096] Identification and area ratio of phases considered as the third hard phase

[0097] Pixels with brightness located on the white side (right side) of the threshold F are considered to belong to the third hard phase or the binding phase. The area fraction of the third hard phase or the binding phase is calculated by dividing the number of these pixels by the total number of pixels.

[0098] To be on the safe side, EPMA analysis was performed at the locations of these pixels to confirm that the composition meets the aforementioned third hard phase.

[0099] Since there is almost no difference in brightness between the third hard phase and the bound phase in SEM images, it is difficult to distinguish between the two phases based on brightness alone. Therefore, EPMA analysis is used to confirm whether it is the third hard phase or the bound phase. The distinction between the third hard phase and the bound phase is based on whether it meets the aforementioned compositional requirements of the third hard phase or whether Co is the main component.

[0100] 3. Manufacturing method

[0101] An example of a method for manufacturing a metal-ceramic cutting tool according to this embodiment will be described.

[0102] 1) Raw material powder

[0103] Prepare TiCN, MCN (M being two or more of Zr, V, Nb, Ta, Mo, and W), Cr3C2, and one or more of Ti, Zr, V, Nb, Ta, Cr, Mo, and W carbides (or composite carbides), W, Co, and Ni with a Fisher particle size of 0.8–3.0 μm.

[0104] By using TiCN powder, a first hard phase of insoluble Cr is formed after sintering; by using MCN powder (as an example, (TiCN) powder)... 0.75 Nb 0.10 Mo 0.05 W 0.10 (CN, a composite carbide powder), the melting point of the hard phase in the matrix of cermet cutting tools is reduced. After sintering, Cr from Cr3C2 no longer exists in the form of Cr3C2 in the hard phase, but exists in solid solution as Cr, thus forming a second hard phase.

[0105] 2) Combination and Mixing

[0106] These raw material powders are combined, for example, in the following manner:

[0107] MCN: 20-50% by weight;

[0108] Cr3C2: 0.5–1.5% by mass;

[0109] Co: 10.0–17.0% by mass;

[0110] TiCN: The remainder.

[0111] Then, in ethanol, a pre-pulverization process is first carried out, in which only Cr3C2 is mixed in a mill for 6 to 20 hours. After that, paraffin and the remaining raw material powder are added and mixed in a mill for 9 to 13 hours to make a slurry.

[0112] By pre-mixing Cr3C2 using a grinding mill, the agglomeration of Cr3C2 can be reduced and Cr3C2 can be finely pulverized. Therefore, Cr from Cr3C2 no longer exists in the form of Cr3C2 in the bonding phase and hard phase of the matrix of cermet cutting tools, but exists in solid solution as Cr, thereby promoting the formation of the second hard phase.

[0113] The obtained slurry is spray-dried using a spray dryer to obtain granulated powder.

[0114] 3) Molding, sintering, and post-treatment

[0115] The obtained granulated powder is pressed into the shape of a specified cutting tool to obtain a molded body. Then, the molded body is sintered.

[0116] Sintering includes the following steps:

[0117] The first heating process involves heating the molded body from room temperature to a first heating temperature of 500-950°C under reduced pressure.

[0118] The second heating process involves raising the temperature from a first heating temperature of 500–950°C to a second heating temperature of 1000–1250°C under a nitrogen atmosphere with a pressure of 1 Torr or higher.

[0119] The third heating process involves raising the temperature from a second heating temperature of 1000–1250°C to a third heating temperature of 1280–1410°C in a vacuum.

[0120] The first holding process is maintained at a third heating temperature of 1280–1410°C;

[0121] The fourth heating process involves raising the temperature from the fourth heating temperature of 1280–1410°C to the fourth heating temperature of 1430–1600°C under a nitrogen atmosphere with a pressure of 5 Torr or higher.

[0122] A second holding step, performed at the fourth heating temperature and in a nitrogen atmosphere at a lower pressure than the fourth heating step, for at least 180 minutes; and

[0123] Cooling process to room temperature.

[0124] By adjusting the nitrogen content in the interior and surface of the matrix of the cermet cutting tool through sintering, a specified hardness distribution can be achieved.

[0125] Then, after sintering, the molded body is cooled and then honed as a post-treatment.

[0126] 4) Film formation of the coating layer

[0127] The coating layer is formed as needed. There are no restrictions on the composition, average thickness, layer structure, or film formation method of the coating layer; known methods can be used. Here, there are no particular limitations on the known coating layers; examples include one or more of the following: Ti carbide layers, nitride layers, carbonitride layers, carbon oxide layers, and carbonitride layers; composite nitride layers or composite carbonitride layers of Ti and Al; and alumina layers.

[0128] Furthermore, the composition of the aforementioned layers is not limited to stoichiometric composition.

[0129] The above description includes the following features.

[0130] (Note 1)

[0131] A cutting tool, comprising a cermet matrix, characterized in that,

[0132] The metal-ceramic matrix comprises a first hard phase, a second hard phase, and a bonding phase.

[0133] The first hard phase is a composite carbonitride comprising 0.0–3.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, 0.0% by mass and less than 0.2% by mass of Cr, 18.0–22.0% by mass of C and N, with the remainder being Ti and unavoidable impurities.

[0134] The second hard phase is a composite carbonitride comprising a total of 10.0–25.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, greater than 0.0% by mass and less than 1.0% by mass of Cr (wherein the Cr content of the second hard phase is higher than that of the first hard phase), a total of 15.0–20.0% by mass of C and N, with the remainder being Ti and unavoidable impurities.

[0135] The bonding phase comprises a total of 0.0% by mass and less than 5.0% by mass of Ni and Fe, 1.0% to 8.0% by mass relative to the Co content, and the remainder is Co and unavoidable impurities.

[0136] In a first region extending 100 μm into the interior of the substrate from the flank face, the Vickers hardness decreases monotonically. In a second region extending 40 μm into the substrate from the flank face, the Vickers hardness is 1700–2100 Hv. In a third region extending 600 μm into the interior of the substrate from the flank face, the Vickers hardness is 1600–1780 Hv.

[0137] (Note 2)

[0138] According to the cutting tool described in Appendix 1, the second hard phase further comprises: Ta and / or Nb; and W.

[0139] (Note 3)

[0140] The cutting tool according to Appendix 1 or 2 is characterized in that it further comprises a third hard phase, said third hard phase being a composite carbonitride comprising a total of 25.0 to 45.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo and W, 0.0% by mass and less than 1.0% by mass of Cr (wherein less than the Cr content of the second hard phase), a total of 10.0 to 17.0% by mass of C and N, the remainder being Ti (wherein less than the Ti content of the first hard phase) and unavoidable impurities.

[0141] (Note 4)

[0142] The cutting tool according to any one of Appendices 1 to 3 is characterized in that the area ratio of the first hard phase is 10.0 to 30.0%, the area ratio of the second hard phase is 50.0 to 80.0%, and the area ratio of the third hard phase is 0.0 to 5.0%.

[0143] (Note 5)

[0144] The cutting tool according to any one of Appendices 1 to 4 is characterized in that the area ratio of the bonding phase in the cross section or the entire surface of the matrix is ​​6.0 to 13.0%.

[0145] (Note 6)

[0146] The cutting tool according to any one of Appendices 1 to 5 is characterized in that the matrix comprises the following: Co: 9.0 to 15.0 wt%, Cr: 0.1 to 1.5 wt%, the total of at least one of Zr, V, Nb, Ta, Mo and W: 10.0 to 40.0 wt%, C: 5.0 to 10.0 wt%, N: 5.5 to 12.0 wt%, and the remainder being Ti and unavoidable impurities.

[0147] Example

[0148] Next, specific examples of applying the cermet cutting tool of the present invention to cutting blades will be described.

[0149] Prepare TiCN and (Ti) with Fisher particle sizes of 0.7–2.3 μm as shown in Table 1. 0.75 Nb 0.10 Mo 0.05 W 0.10 CN, (Ti 0.75 Ta 0.10 Mo 0.05 W 0.10 CN, (Ti 0.77 Mo 0.08 W 0.15 CN, (Ti 0.90 W 0.10 CN, (Ti 0.75 Nb 0.15 W 0.10 CN, (Ti 0.77 Mo 0.08 W 0.15 CN, (Ti 0.77 Nb 0.10 Cr 0.03 W 0.10CN, Cr3C2, VC, W, NbC, ZrC, Co, and Ni powders were prepared so that they could be formulated according to the formulations in Table 1. Then, in ethanol, only Cr3C2 was milled and mixed for 6 hours, followed by the addition of paraffin and the remaining raw material powders, and milled and mixed for 11 hours to prepare a slurry.

[0150] The slurry was dried using a spray dryer, and then the compound composition was pressed into a powder to produce molded bodies for the examples and for the comparative examples.

[0151] The molded body is then sintered.

[0152] The thermal histories of both the embodiments and comparative examples are described below, wherein the pressure atmospheres of the first holding process and the second holding process are set differently.

[0153] In the first heating process, the molded body is heated from room temperature to 600°C under reduced pressure.

[0154] In the second heating step, the temperature is raised to 1200°C in a nitrogen atmosphere of 3.0 Torr.

[0155] In the third heating process, after heating to a third heating temperature of 1400℃ in a vacuum,

[0156] In the first holding step, the temperature is maintained for 30 minutes in a nitrogen atmosphere of 2.0 Torr.

[0157] Subsequently, in the fourth heating step, the temperature is raised to 1490°C in a nitrogen atmosphere of 0.5 Torr or 10.0 Torr.

[0158] In the second holding step, the temperature is maintained for 210 minutes in a nitrogen atmosphere of 0.5 Torr or 1.0 Torr (the atmosphere pressures for the fourth heating step and the second holding step are recorded in Table 2).

[0159] Then, cool to room temperature.

[0160] Next, the sintered body was honed to produce blades with CNMG120408 (with chip breakers) as shown in Tables 3 to 6: Examples 1 to 11 and Comparative Examples 1 to 6.

[0161] Tables 3 to 6 show the area fraction of each hard phase and the analytical results of the bound phase. The area fraction and bound phase were determined according to the methods described above.

[0162] The SEM reflection electron image was taken under conditions of accelerating voltage of 10kV, irradiation current of 30nA, and magnification of 5000x.

[0163] In addition, the determination conditions for EPMA are as follows.

[0164] Point analysis (analyzing the composition of each phase): Set the observation field of view to 9μm vertically and 12μm horizontally, set the accelerating voltage to 8kV, the irradiation current to 20nA, the beam diameter to φ0μm, and the counting time to 300sec.

[0165] Surface analysis (analysis of the area ratio of the bound phase): set the observation field of view to 18μm vertically and 24μm horizontally, set the magnification to 5000x, the accelerating voltage to 10kV, the irradiation current to 30nA, the pixel spacing to 0.1μm, and the counting time for each point to 30mSec.

[0166] The spectroscopic crystals used for each element in point and area analysis are: CK α LDE2H, NK α LDE1H, TiK α :LIFH, CoL α TAPH, WM α :TAP.

[0167] [Table 1]

[0168]

[0169] In Table 1, the Fisher particle size is listed above the name of the raw material powder, and "-" indicates that it is not compounded.

[0170] [Table 2]

[0171]

[0172] [Table 3]

[0173]

[0174] [Table 4]

[0175]

[0176] [Table 5]

[0177]

[0178] [Table 6]

[0179]

[0180] [Table 7]

[0181]

[0182] In Table 7, "Vickers hardness (Hv) at each distance from the outermost surface segment" is the value obtained according to the aforementioned Vickers hardness measurement method, which represents "Vickers hardness (Hv) at each distance from the surface of the substrate".

[0183] As can be seen from Tables 1 to 7,

[0184] Although Example 1 and Comparative Example 1 are molded bodies with the same formulation, the Vickers hardness at 10 μm and 40 μm from the surface of the substrate does not decrease monotonically due to the different atmosphere pressures in the first holding process.

[0185] The Vickers hardness of Comparative Example 2 at a depth of 600 μm from the surface of the substrate is less than 1600 (Hv).

[0186] The second hard phase of Comparative Example 3 does not contain Cr.

[0187] The total content of Zr, Nb, Ta, V, W, and Mo in Comparative Example 4 exceeded 25% by mass.

[0188] In Comparative Example 5, the combined C and N content in the second hard phase is less than 15.0% by mass, the combined Ni and Fe content in the bound phase exceeds 5.0% by mass, and the Cr content relative to the Co content in the bound phase exceeds 8.0%.

[0189] The combined content of Ni and Fe in the bonding phase of Comparative Example 6 exceeds 5%, and the Vickers hardness at 10 μm from the surface of the back face of the matrix into the matrix exceeds 2100 Hv, and the Vickers hardness at 600 μm exceeds 1780 Hv.

[0190] Next, wear resistance tests were conducted on each sample under the following conditions, and the wear width of the back face was measured after 20 minutes.

[0191] <Cutting conditions for wear resistance test>

[0192] Workpiece: SNCM439

[0193] Cutting speed: 250 m / min

[0194] Depth of cut: 0.5mm

[0195] Rotary feed rate: 0.1 mm / rev

[0196] Coolant: Water-soluble

[0197] In addition, a damage resistance test was conducted on each sample under the following conditions to confirm whether the cutting tool was damaged after 1 minute of processing.

[0198] <Cutting conditions for damage resistance test>

[0199] Workpiece: SCM440

[0200] Workpiece shape: A round bar with four equally spaced grooves on its outer circumference.

[0201] Cutting speed: 200m / min

[0202] Depth of cut: 1.0mm

[0203] Rotary feed rate: 0.1 mm / rev

[0204] Coolant: None

[0205] [Table 8]

[0206]

[0207] As shown in Table 8 of the aforementioned wear resistance and chipping resistance tests, the flank wear width of the examples was small and the blades exhibited durability. Furthermore, no tip chipping occurred in the chipping resistance evaluation. On the other hand, the comparative examples had larger flank wear widths, poorer durability, or tip chipping occurred in the chipping resistance evaluation.

[0208] The embodiments disclosed above are merely exemplary in all respects and are not restrictive. The scope of the invention is defined by the claims, not by the foregoing embodiments, and is intended to include all modifications within the meaning and scope of the claims.

[0209] Explanation of reference numerals in the attached figures

[0210] 1 First hard phase

[0211] 2 Second hard phase

[0212] 3. Binding phase

[0213] 4 Third hard phase

[0214] 10. Rake face (substrate surface)

[0215] 11 Angle φ

[0216] 12 Grinding section

[0217] 13 Unground section

[0218] X segment X

[0219] S is the outermost line segment

[0220] Line segment A

[0221] Line segment B

[0222] Line segment C

[0223] Line segment D

[0224] a~d Vickers hardness testing points (indentations)

Claims

1. A cutting tool, comprising a cermet matrix, characterized in that, The metal-ceramic matrix comprises a first hard phase, a second hard phase, and a bonding phase. The first hard phase is a composite carbonitride comprising 0.0–3.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, 0.0% by mass and less than 0.2% by mass of Cr, 18.0–22.0% by mass of C and N, with the remainder being Ti and unavoidable impurities. The second hard phase is a composite carbonitride comprising 10.0–25.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, greater than 0.0% by mass and less than 1.0% by mass of Cr, and 15.0–20.0% by mass of C and N, with the remainder being Ti and unavoidable impurities. The Cr content of the second hard phase is higher than that of the first hard phase. The bonding phase comprises a total of 0.0% by mass and less than 5.0% by mass of Ni and Fe, 1.0% to 8.0% by mass relative to the Co content, and the remainder is Co and unavoidable impurities. In a first region extending 100 μm into the interior of the substrate from the flank face, the Vickers hardness decreases monotonically. In a second region extending 40 μm into the substrate from the flank face, the Vickers hardness is 1700–2100 Hv. In a third region extending 600 μm into the interior of the substrate from the flank face, the Vickers hardness is 1600–1780 Hv.

2. The cutting tool according to claim 1, characterized in that, The second hard phase further comprises: Ta and / or Nb; and W.

3. The cutting tool according to claim 1 or 2, characterized in that, The compound further comprises a third hard phase, which is a composite carbonitride containing a total of 25.0 to 45.0% by mass of at least one selected from Zr, V, Nb, Ta, Mo, and W, 0.0% by mass and less than 1.0% by mass of Cr, a total of 10.0 to 17.0% by mass of C and N, with the remainder being Ti and unavoidable impurities. The Cr content of the third hard phase is less than that of the second hard phase, and the Ti content of the third hard phase is less than that of the first hard phase.

4. The cutting tool according to claim 1 or 2, characterized in that, The area fraction of the first hard phase is 10.0-30.0%, the area fraction of the second hard phase is 50.0-80.0%, and the area fraction of the third hard phase is 0.0-5.0%.

Citation Information

Patent Citations

  • Electric rotary apparatus

    JP1981044388A

  • Configurable distributed interlock system

    JP2024054388A